The THE EVALUATION OF CURRICULUM 2013 IMPLEMENTATION TOWARDS HISTORY LEARNING USING COUNTENANCE STAKE'S MODEL IN SENIOR HIGH SCHOOL - Bayu Tri Prasetyo; Nurul Umamah; Sumardi Sumardi; Riza Afita Surya (JURNAL HISTORICA, 2021)
The curriculum 2013 has been implemented in Indonesia since 2013. However, its success is still questionable. The 2013 curriculum was developed with a different pattern of improvement from the previous curriculum. This study aims to evaluate the implementation of the 2013 curriculum using the Countenance Stake model which includes evaluation of antecedent, transaction, and outcomes. The data collection techniques used were observation, interview, questionnaire, and documentation. Data analysis was performed using quantitative descriptive analysis techniques. The purpose of this study was to determine the success of the 2013 curriculum implementation in history learning. The results of the evaluation from the implementation of the learning program show that: (1) there are still many historical learning needs that have not been fulfilled maximally so that it encourages many problems in learning history, (2) history learning planning (RPP) established by all historical educators with percentage of 100% gained a score between 28 to 42, there by it is in the moderate category or quite appropriate and respondents assessment of history learning process implementation received a percentage 94,4% in the moderate or sufficient category in accordance with the standard education process based on the 2013 curriculum; (3) the learning outcomes of students history catagorized as quite good, because the average is above the minimum criteria of mastery learning (KKM) Therefore, the learning process at senior high school needs to be improved considering that there are still obstacles that occur in the learning process.